Berberine Inhibits Growth and Induces G1 Arrest and Apoptosis in Human Cholangiocarcinoma QBC939 Cells - Wei He; Bin Wang; Yun Zhuang; Dong Shao; Kewen Sun; Jianping Chen (Elsevier, 2012)
The chemotherapeutic approach using non-toxic natural products may be one of the strategies for the management of the cholangiocarcinoma. Here we report that in vitro treatment of human cholangiocarcinoma QBC939 cells with berberine, a naturally occurring isoquinoline alkaloid, decreased cell viability and induced cell death in a dose-dependent manner, which was associated with an increase in G1 arrest. Our western blot analysis showed that berberine-induced G1 cell cycle arrest was mediated through the increased expression of cyclin-dependent kinase inhibitors (Cdki) proteins (Cip1/p21 and Kip1/p27); a simultaneous decrease in Cdk2 and Cdk4 and cyclins D1, and reduced activity of the Cyclins-Cdk complex. In additional studies, treatment of QBC939 cells with different concentrations (10, 40, 80 μM) of berberine for 48 h resulted in a significant dose-dependent increase in apoptosis compared to the non-berberine-treated control, which was associated with an increased expression of pro-apoptotic protein Bax and decreased expression of anti-apoptotic proteins Bcl-2 and Bcl-xL. Together, this study for the first time identified berberine as a chemotherapeutic agent against human cholangiocarcinoma cells QBC939 cells in vitro. Further in vivo studies are required to determine whether berberine could be an effective chemotherapeutic agent for the management of cholangiocarcinoma. Keywords:: berberine, cholangiocarcinoma, cell cycle, cyclin-dependent kinase inhibitor, apoptosis